Water Industry (Law) Reforms: The Adoption of Australian Drinking Water Guidelines in Western Australia — From Targets to Aspirations. Issue 2 (1st March 2015) - Coles, Neil
Abstract : The past two decades have overseen a dramatic shift in the way Australians view water resources, their value, and the way in which it is allocated and managed. Water law and regulatory reforms within government and industry at National and State levels have resulted in unprecedented changes in the way governments, councils, and corporate bodies are structured to manage it. Although Western Australia has been at the forefront of the planning and regulatory reforms required to manage two decades of declining rainfall and expanding population, much of the reform is driven by the National agenda. Modifications in water policy, water industry re‐structure, and water supply and drinking water quality guidelines were introduced with this reform agenda. This paper evaluates the changes in the water industry, and in the way in which water resources are managed and water is licensed and regulated to deliver quality drinking water through the framework of the Australian Drinking Water Guidelines in Western Australia.